An 8-week ramdomized trial on the effectiveness of Modified Protein Diet (MPD) and the Standard Diabetid Diet (SDD) on blood sugar levels of adult type 2 diabetics - Liwag, Aretha Ann C. Gacutan
Introduction: Diabetes affects atleast 2.8 M Filipinos and this is projected to increase by epidemic proportions by the year 2025. Standards of medical care for diabetes include medical nutrition therapy, exercises and medications, to address treatment goals in near normalization of blood glucose and lipid levels to prevent associated chronic complications. This study aims to compare the effectiveness of a modified protein diet (MPD) in decreasing fasting glucose levels to 120 mg/dl, after 8 weeks of treatment as compared to the standard diabetic diet (SDD) in adult DM2 patients. Methods : This is an 8-week randomized trial among DM2 patients seen at the outpatient department of the West Visayas State University Medical Center from March to July 2006. Regular dietary counseling and documentation were done by nutritionists during the whole study period. Anthropometric and metabolic parameters were measured at baseline and after eight weeks of treatment. Dietary recording by food dairies and food frequency questionnaires were done to validate adherence to the diet. Results: A total of twenty six patients were enrolled and randomized to the MPD (n=13) and the SDD (n=13) groups. Except for the decrease in triglyceride levels among SDD group, there was no significant difference in the proportion of patients who achieved treatment guideline goals between treatment groups. There was lower intake of protein, fats and total caloric intake among the MPD group as compared to the SDD group. Conclusions: There was no sufficient evidence to show that a modified protein diet significantly decrease fasting blood glucose levels to 120 mg/dl among adult DM2 patients as compared to the standard diabetic diet. Except for a significant decrease in triglyceride levels in the SDD group, there was no significant difference in the proportion of patients who achieved treatment guidelines, and decrease in oral gypoglycemic agent doses between treatment groups. There was lower fat and protein intake reported, as well as compliance to the prescribed dietary components in the MDP group as compared to the SDD group. The patients on the MPD had lower fish intake reported as compared to the SDD. Higher reported consumption of index food items, index food groups and fried fish did not affect the proportion of patients achieving treatment goals.
Thesis--Master of Science in Clinical Epidemiology--University of the Philippines Manila.
Keywords: Diabetes; Modified Protein Diet (MPD).; Standard Diabetic Diet (SDD).